Ajowan Oil Potentiates Ros-mediated Teratogenic Effect in Zebrafish Embryos. Issue 4 (4th July 2017) - Kim, Sang Ho; Sharma, Chanchal; Kang, Sun Chul
Abstract: Ajowan ( Trachyspermum ammi ) has been widely used in foods, drugs and cosmetics, but their applications as a pesticide are of increased concern. Ajowan is described as toxic to spermatogenesis and cause teratogenic effect in rat fetus but their influence on teratogenicity remains vague. This intended us to investigate the development effects of ajowan oil (AJO) on zebrafish embryo-larval stages. Primarily, we evaluated the chemical composition of AJO GC-MS and we identified nearly 20 compounds representing 93.82% of the whole oil. Next, we investigated the dose-dependent (5, 15 and 30 μg/mL) eco-toxicological impact of AJO on zebrafish embryos for 96 hours post fertilization (hpf), we found that AJO potentially inducing delayed hatching, retarded heart rate and phenotypic malformations in zebrafish embryos associated with reduced survival rate (LC50 =17.8 μg/mL) when compared to control embryos. Evidence from 2′, 7′ -dichlorofluorescin diacetate (DCFH-DA), acridine orange (AO) and Casp-3 immunofluorescence staining clear cuts AJO strongly provoked ROS generation and apoptotic events in response to oxidative damage. Furthermore, the expressions of SOD-1, CAT and apoptotic markers (Bax, Cytochrome-C, p53, Casp-3 and Casp-9) was dose-dependently (P<0.05) upregulated along with downregulated Bcl-2 and PARP1 (Necrotic marker) levels in AJO embryos. Collectively, our findings confirmed that AJO cause severe teratogenic and apoptotic events to zebrafish embryos, likely due an overwhelming ROS biogenesis.